The Importance Of Implementing Effective Management Mechanisms In Educational Organizations - Mamayusupova Muattar Qosimjonovna (Euro Asian Journal Publishing, 2025)
This article analyzes the importance of implementing effective management mechanisms in general secondary schools. The main directions of effective management, such as strategic planning, development of material and technical base, working with teachers, cooperation with parents, and evaluating educational outcomes, are highlighted. Practical recommendations aimed at improving the effectiveness of schools are provided in the article.
Keywords: education quality; management mechanisms; general secondary education; strategic planning